2021
DOI: 10.1371/journal.pone.0259680
|View full text |Cite
|
Sign up to set email alerts
|

The structure, centrality, and scale of urban street networks: Cases from Pre-Industrial Afro-Eurasia

Abstract: Cities and towns have often developed infrastructure that enabled a variety of socio-economic interactions. Street networks within these urban settings provide key access to resources, neighborhoods, and cultural facilities. Studies on settlement scaling have also demonstrated that a variety of urban infrastructure and resources indicate clear population scaling relationships in both modern and ancient settings. This article presents an approach that investigates past street network centrality and its relation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 56 publications
0
1
0
1
Order By: Relevance
“…trabalhos tem investigado a influência de características e medidas de redes de rua no contexto de mobilidade urbana, como [Tokuda et al 2022], [Tsiotas and Polyzos 2017], [Geng and Zhang 2023] e [Altaweel et al 2021]. No entanto, em todos esses trabalhos, são consideradas escalas de redes que contemplam cidades ou regiões maiores, o que muitas vezes pode fazer passar despercebidas as variac ¸ões dessas características de redes quando consideramos estruturas com menor granularidade.…”
Section: Diversosunclassified
“…trabalhos tem investigado a influência de características e medidas de redes de rua no contexto de mobilidade urbana, como [Tokuda et al 2022], [Tsiotas and Polyzos 2017], [Geng and Zhang 2023] e [Altaweel et al 2021]. No entanto, em todos esses trabalhos, são consideradas escalas de redes que contemplam cidades ou regiões maiores, o que muitas vezes pode fazer passar despercebidas as variac ¸ões dessas características de redes quando consideramos estruturas com menor granularidade.…”
Section: Diversosunclassified
“…Derrible [ 44 ] demonstrated how betweenness centrality can provide insights for designing infrastructure systems. Altaweel et al [ 45 ] investigated the relationship between future population scaling and past node centrality in a network. Demšar et al [ 46 ] found a strong correlation between streets with high betweenness and highways/main roads in the Helsinki Metropolitan area.…”
Section: Introductionmentioning
confidence: 99%